PRODUCTION PERFORMANCE OF KHAKI CAMPBELL DUCKS IN BACKYARD SYSTEM AND ITS ECONOMICS IN ASSAM STATE OF INDIA - F.U.A. Ahmed; M. Doley; M. Rahman; B.K. Das; B.J. Gharphalia; A. Paul; G.K. Sarma; P.K. Pathak; R.K. Saud; M. Neog; C.K. Deka; R. Islam (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted in four flood-prone villages at Krishi Vigyan Kendra, Assam Agricultural University, Dhubri to assess the production performance of Khaki Campbell ducks and the economics of rearing them under NICRA (National Innovations in Climate Resilient Agriculture) project. A total of 10 farmers were selected from Dhubri village on the basis of their experience in duck farming. Two hundred day-old Khaki Campbell ducklings, twenty numbers irrespective of sex per household, were distributed and reared up to 72 weeks. On attaining 30th week of age, the male ducks were sold out. The data including body weight, mortality, age at first egg and egg production were recorded. The average age at first egg was 163.0±3.6 days, and 30th week mean body weight was 1.8±0.1 kg. The mean egg production and mortality rate were 180.8±4.1 and 13% respectively during the study period. It was found from the study that Khaki Campbell duck farming has contributed notably to the livelihood of the rural farmers with benefit-cost ratio of 1.87.